Impact of Revenue Diversification on Bank Profitability and Stability: A Case of Nepalese Commercial Banks - Devkota, Ankit (Nepalese Journal of Economics, 2024)
This study examines the impact of revenue diversification on the financial profitability and stability of Nepalese commercial banks. Return on assets (ROA) and Z-score are the selected dependent variables. The selected independent variables are bank size, non-interest income to total assets, capital adequacy ratio, gross domestic product growth rate, operating income expenses ratio and credit risk. The study is based on secondary data of 16 commercial banks with 128 observations for the study period from 2013/14 to 2020/21. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of revenue diversification on the financial profitability and stability of Nepalese commercial banks. The study showed that credit risk has a negative impact on return on assets and Z-score. It indicates that increase in non-performing loan leads to decrease in return on assets and Z-score. Similarly, capital adequacy ratio has a positive impact on return on assets and Z-score. It indicates that increase in capital adequacy ratio leads to increase in return on assets and Z-score. Likewise, non-interest income to total assets has a positive impact on return on assets and return on equity. It indicates that increase in non-interest income to total assets leads to increase in return on assets and return on equity. In contrast, gross domestic product growth rate has a positive impact on return on assets and return on equity. It indicates that higher the gross domestic product growth rate, higher would be the return on assets and return on equity. In addition, bank size has a positive impact on Z-score. It indicates that increase in bank size leads to increase in Z-score. Moreover, operating income expenses ratio has a positive impact on return on assets and return on equity. It indicates that increase in operating income expenses ratio leads to increase in return on assets and Z-score.